2020
DOI: 10.1371/journal.pone.0239665
|View full text |Cite
|
Sign up to set email alerts
|

Early readmission and its predictors among patients treated for acute exacerbations of chronic obstructive respiratory disease in Ethiopia: A prospective cohort study

Abstract: Background Significant numbers of chronic obstructive respiratory disease patients are readmitted for Acute Exacerbation (AE) within 30 days of discharge. And these early readmissions have serious clinical and socioeconomic consequences. The objective of our study was to determine the rate of readmission within 30 days of discharge and it's predictors among patients treated for acute exacerbations of asthma and chronic obstructive pulmonary disease (COPD). Methods A prospective cohort study involving 130 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…None of the selected articles described the risk of bias for random sequence generation, allocation concealment, blinding of participants and researchers, or blinding of outcome assessment, so the above biases were all considered low-risk. Two articles had a high risk of bias from incomplete result data (14,17), and 5 articles had a low risk of bias from incomplete result data (12,13,15,16,18). Selective reporting domains and other biases for all articles were low-risk (Figure 7).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…None of the selected articles described the risk of bias for random sequence generation, allocation concealment, blinding of participants and researchers, or blinding of outcome assessment, so the above biases were all considered low-risk. Two articles had a high risk of bias from incomplete result data (14,17), and 5 articles had a low risk of bias from incomplete result data (12,13,15,16,18). Selective reporting domains and other biases for all articles were low-risk (Figure 7).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Since the publication of our systematic review, we have updated our search and identified six additional studies (418)(419)(420)(421)(422)(423). Generally, all the reported risk factors found in these additional studies were identified in our previous systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, all the reported risk factors found in these additional studies were identified in our previous systematic review. Anbesse et al conducted a prospective study and found that frequent admissions and the use of long-term oxygen to be associated with 30-day readmission (418). Similarly, another prospective study reported limitation in performing basic activities of daily living and frequent admissions for COPD exacerbations to be associated with risk of readmission at 30 and 90 days (419).…”
Section: Discussionmentioning
confidence: 99%
“…If the target is directed more at the pharmaceutical management, the effect on LOS will be indirect. The efficiency of the pharmaceutical department can affect LOS by ensuring drug certainty and quality (Galli et al, 2016), ensuring drug availability (Tefera et al, 2020), ensuring drug adherence (Monfort et al, 2016), preventing drug poisoning (Chelkeba et al, 2018) and providing assistance in the patient care (Anbesse et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%